Childhood unintentional burn prevention: knowledge and practices among caretakers in a semi-urban community in Sri Lanka - Dilshan Wijeratne; Ranjith Batuwanthudawe (College of Community Physicians of Sri Lanka, 2017)
Background: Accidental burns are a common cause of morbidity and mortality among children under 5 years. The principal caretaker's knowledge and practices are directly associated with the child's safety. Objective: To describe the knowledge and practices on childhood unintentional burns prevention among principal caretakers of under 5 year children in a semi-urban community. Method: This community-based cross-sectional study was conducted on 462 principal caretakers of children below 5 years in Chilaw MOH area. Multi-stage cluster sampling technique was used. Caretaker's knowledge and practices related to unintentional burns prevention were measured using a pre-tested interviewer-administered questionnaire. Multiple linear regression analyses were used to identify socio-demographic factors associated with caretaker's knowledge and practices. Results: In 90.5% household's mother was the principal caretaker. The median age of principal caretakers was 27 years (lQR; 24-31years). The mean scores for overall knowledge and practices were 75.8% (±11.2%) and 67.6% (±12.8%) respectively. Three-quarters of principal caretakers were aware that children are more vulnerable for burns while 63.1% caretaker's believed accidental burns are preventable. Over 70% of caretakers knew that many injuries can be avoided by stopping children coming to the kitchen, but only in 39.2% houses had safety barriers preventing children coming to the kitchen. Two-thirds of the principal caretakers always ensured that their children were under close supervision. The caretakers overall knowledge was significantly associated with their education level (p<0.001), caretaker's relationship to the child (p=0.002) and family income (p=0.038). The practices related to burn prevention was significantly associated with caretaker's education level (p<0.001), family income (p=0.006), and social class (p=0.011). Conclusion: Young children spend most of their time in households; still there are many hazards around them which can lead to accidental burns. This study identified a gap between caretakers' knowledge and practices which need targeted interventions to safeguard children.